Awareness and Perception of Academicians on the Use of Turnitin Software in Detecting Plagiarism in Bayero University Kano - CLN, Kabiru Danladi Garba (African Journal of Education,Science and Technology (AJEST), 2018)
The effect of plagiarism has brought a lot of academic dishonesty among the academicians. The effect is directly related to the millions of electronic resources on the internet. Plagiarism affects not only the academic staff but the integrity of the University. Turnitin is a web-based software that is used for plagiarism detection and is meant to aid and promote originality of research publications. Despite the importance attached to this software, many academicians in Bayero University Kano have partial knowledge about the software and the extent of its use to detect plagiarism. The researcher investigated the level of awareness and perception of Turnitin in detecting plagiarism misdemeanors in Bayero University Kano. The study was quantitative and used the survey research method for data collection using a questionnaire. A sample of 150 respondents of academic staff was used. The findings revealed that the level of awareness on the existence of the software among the academicians of Bayero University Kano is average. But the extent of how the software is used in detecting plagiarism is significantly low. To overcome these problems, the study recommends awareness campaigns and training on how to use Turnitin software by the University management.